Liquidity picking and fund performance - Jiao, Feng; Sarkissian, Sergei; Schumacher, David (Journal of Financial Economics, 2025)
Using global mutual fund and American Depositary Receipt (ADR) data, we test if funds strategically trade cross-listed firms’ equity shares in the most liquid trading location. We find that especially funds that score high on traditional skill measures exhibit a liquidity-based trading venue preference. We identify an informed trading motive as the most likely driver for such behaviour rather than preference based on geographic, economic, cultural, or governance motives. Thus, liquidity picking is associated with fund outperformance and stock selection ability that is not limited to only cross-listed firms. Our tests directly support theories of informed trading in a multi-market setting.